Effects of hydrological dynamics in controlling phosphorus bioavailability in intermittent rivers and implications for estuaries - da Silva, Antonio Elves Barreto; Queiroz, Hermano Melo; de Oliveira, Daniel Pontes; Nóbrega, Gabriel Nuto; Pereira, Tamara Maciel; de Freitas Lima, Paulo; Barcellos, Diego; Rezende, Carla Ferreira; Ferreira, Tiago Osório (Frontiers in Water, 2024)
Several studies on intermittent rivers and ephemeral streams (IRES) have focused on the ecology of populations and communities, and very few explored the biogeochemistry and bioavailability of key elements, such as phosphorus (P) and nitrogen (N). In this study, we aimed to explore the role of environmental seasonality on P bioavailability in an intermittent river in Northeastern Brazil and the implications for nutrient dynamics to downstream ecosystems, such as the estuaries. The study was performed at the Cruxati River, located in the Litoral Hydrographic Basin on the coast of Ceará State, Brazil. We sampled riverine sediments during three hydroperiods (i.e., dry, rewetting, and flow) according to the theoretical model for research in intermittent rivers. We performed a geochemical fractionation of different P forms and determined the physicochemical parameters, particle size distribution, mineralogy, and total organic carbon of the sediments. Mean values were compared using the Kruskal–Wallis non-parametric statistical test (p-value < 0.05) and by discriminant function analysis. We observed that the predominant fractions of P were associated with Fe-oxides, silicates, and refractory organic matter, but there were no statistical differences among these fractions for all hydroperiods. The exchangeable-P form was higher in the dry and flow periods than in the rewetting period. On the opposite side, P associated with humic acids and carbonates was lower in the dry and flow periods but higher in the rewetting period. We concluded that seasonality influences the bioavailability of P in intermittent rivers, being strongly influenced by the organic fraction, including the humic acid fraction and the refractory organic matter, which are important sources of P in the aquatic system. Furthermore, the IRES may act as a source or a sink of nutrients throughout the cycles of wetting and drying, which may release P from the sediments to the aquatic environment. Hence, IRES plays an important role in transporting nutrients to estuaries and maintaining their ecosystem services.